The Effectiveness of Acceptance and Commitment Therapy on Marital Functioning and Marital Conflicts in Couples with a Tendency toward Emotional Divorce - Kazemi Dogolsar , Fatemeh; Ahmadpour Hoseinzadeh , Masumeh; Karbalaei Farajollah Tehrani , Shayan; Majlesi , Zeinab; Abolfathi Doyran, Leila (KMAN Counseling & Psychology Nexus, 2024)
The present study aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on marital functioning and marital conflicts in couples with a tendency toward emotional divorce. The research employed a quasi-experimental method using a pre-test–post-test design with a control group. The statistical population included couples with a tendency toward emotional divorce who sought counseling services in Tehran during the year 2023. Using a convenience sampling method, 28 couples were selected and randomly assigned to the experimental group (14 couples) and the control group (14 couples). Data were collected using the Marital Functioning Questionnaire and the Marital Conflict Questionnaire. The participants in the experimental group received Acceptance and Commitment Therapy over eight weekly sessions, each lasting 90 minutes, while the control group received no specific intervention. The findings after the intervention showed that, in the experimental group, the post-test scores for marital functioning and marital conflicts were significantly improved compared to the pre-test scores. Therefore, Acceptance and Commitment Therapy has a significant impact on marital functioning and marital conflicts in couples with a tendency toward emotional divorce.